From opportunities to innovation: How HR practices, engagement, personality, and autonomy drive creative performance? - Dewi, Puspa; Alviani, Devi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study aims to examine the influence of opportunity-enhancing HR practices on employees’ creative performance, with work engagement as a mediating variable and proactive personality and job autonomy as moderating variables. The research addresses a gap in the literature, which often overlooks internal linkages among HR system components, particularly the role of opportunity-enhancing practices in translating employee potential into actual performance. The study involved 214 employees selected from a total population of 482 employees working in the palm oil mill industry in Riau Province, using systematic random sampling. Data were collected through a survey and analyzed using structural equation modeling (SEM) with SmartPLS 3.0. The results indicate that opportunity-enhancing HR practices positively affect creative performance through the mediating role of work engagement. Employees’ proactive personality strengthens this indirect effect. However, job autonomy does not significantly moderate the relationship between engagement and creative performance. Grounded in the componential theory of creativity and the conservation of resources theory, these findings provide practical insights for organizations aiming to foster innovation and sustain competitive advantage through targeted HR practices.